Brain morphometry and Seed-based analysis of resting-state functional connectivity in default mode network of Alzheimer's disease patients compared with healthy control subjects in the Klang Valley, Malaysia - Mohad Azmi, N. H.; Suppiah, S.; Ibrahim, N. S. N.; Ibrahim, B.; Seriramulu, V. P.; Piersson, A. D.; Mohamad Aznan, M. N.; Karuppiah, T.; Omar, N. F.; Ibrahim, N.; Razali, R. M.; Harrun, N. H.; et al. (Elsevier, 2022)
The default mode network (DMN) is a large brain network in the human brain and has a substantial correlation with Alzheimer's disease (AD). Grey matter volume (GMV) and functional connectivity (FC) were reported to be different between AD and healthy control (HC). Nevertheless, the structural and functional alterations that take place in AD in association with the DMN in Malaysian patients is not well understood. Our aim was to show how structural MRI data could be processed using voxel-based morphometry (VBM) to identify differences in regional grey matter volume (GMV) between AD patients and HC. Comparison of the variations in rs-functional connectivity in the DMN on fMRI scans between AD and HC was another objective of this study.